STATISTICAL CONTROL OF PRODUCTION PROCESSES, ANALYSIS OF THE MEASUREMENT SYSTEM (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
this article covers the improvement of the concepts of responsibility and commitment of enterprises producing basalt products in the satisfaction of demand and desire of their consumers and stakeholders, as well as in the achievement of their involvement in the provision of products and services.